Ineffective training, free-radical formation and low protein diet in Polish Sportsmen - Matuszkiewisz, A.; Kaczor, J. J.; Ratkowski, W.; Popinigis, J.; Hackney, A. C. (Medycyna sportowa, 2001)
The demand for protein in the diet of sportsmen is higher than that of sedentary individuals. According to Colgan (1993), the dietary requirement is approximately 1.4 g protein per kilogram of body mass per day (g/kg/d) in endurance trained, 1.7 g/kg/d in sprint trained, and 2.0g/kg/d in strength trained sportsmen. In contrast, sedentary men require approximately 0.9 g/kg/d. The key reason for this enhanced dietary intake appears related to training induced adaptations with respect to an increased protein turnover rate (i.e., synthesis; Lemon 1996). Coaches in Poland have wondered whether inadequate dietary protein intake could be a causative factor for some incidences of ineffective training seen in athletes. To address this issue we conducted a two-part study.